PERANCANGAN SISTEM INFORMASI PENDAFTARAN SISWA BERBASIS WEB DENGAN METODE WATERFALL PADA SMP UNIVERSE - Steven Kurniawan; Alkianu Zibran; I Komang Yoga (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
This study aims to design and develop a web-based information system specifically tailored to streamline the new student enrollment process at SMP Universe. The system allows prospective students and their parents to register online conveniently and practically using their devices without the need to visit the school in person. It provides not only digital registration forms but also features for uploading supporting documents and monitoring the registration status in real time. The Waterfall methodology was employed to ensure that each stage—ranging from requirement analysis, system design, implementation, to testing—is carried out systematically and comprehensively. This system is expected to make the enrollment process more efficient, transparent, and enhance user satisfaction. Based on the research findings, it can be concluded that the system not only simplifies the administrative process of registration but also contributes to a more organized and modern student data management.